Performance evaluation of buried pipe under loading using fiber Bragg grating and particle image velocimetry techniques. (December 2021) - Wang, De-Yang; Zhu, Hong-Hu; Wang, Bao-Jun; Shi, Bin
Graphical abstract: Highlights: Soil failure surfaces are categorized as logarithmic spiral, linear and logarithmic. Establish two methods to calculate the ultimate capacity of the soil-pipe system. Propose a simple method to compute the pipe radial displacement using FBG strain measurements. Abstract: Accurate and real-time estimation of underground pipelines' response to external loads is essential, in which the fiber Bragg grating (FBG) technique has shown great potential. A series of 1-g plane strain model tests were conducted to investigate the feasibility of using FBG sensors for monitoring the behavior of the soil-pipe system under surcharge loadings, while particle image velocimetry (PIV) was employed to measure the soil shear strain fields. The test results show three types of soil failure surfaces, i.e., logarithmic spiral, linear, and logarithmic. Regarding various failure modes, two theoretical methods to estimate the ultimate bearing capacity of the soil-pipe system are introduced. Detailed discussions are presented regarding the evolution of pipe strain measurement under different ground settlements. Finally, a method is proposed to calculate the radial displacements based on strain measurements for a shallowly buried pipe and a relative error below ±10% is obtained in this study.